An introduction to the civil registration and vital statistics systems with applications in low- and middle-income countries - Samuel Mills; Jane Kim Lee; Bahie Mary Rassekh (BMC, 2019)
Abstract In collaboration with development partners, the World Bank Group (WBG) has been working to strengthen civil registration and vital statistics (CRVS) systems in low- and middle-income countries through lending operations, technical assistance projects, advisory services and analytics, and knowledge sharing at various international, regional, and national conferences and fora and through publications. In 2017, it launched a comprehensive CRVS eLearning course, which provides practical tools and approaches to achieving twenty-first-century state-of-the-art CRVS systems that are linked to identity management systems and are tailored to local contexts. Some of the key lessons learned from the various initiatives and projects are presented in the eight peer-reviewed manuscripts included in this issue.